Developing brain under renewed attack: viral infection during pregnancy - Recaioglu, Hatice; Kolk, Sharon M. (Frontiers in Neuroscience, 2023)
Living in a globalized world, viral infections such as CHIKV, SARS-COV-2, and ZIKV have become inevitable to also infect the most vulnerable groups in our society. That poses a danger to these populations including pregnant women since the developing brain is sensitive to maternal stressors including viral infections. Upon maternal infection, the viruses can gain access to the fetus via the maternofetal barrier and even to the fetal brain during which factors such as viral receptor expression, time of infection, and the balance between antiviral immune responses and pro-viral mechanisms contribute to mother-to-fetus transmission and fetal infection. Both the direct pro-viral mechanisms and the resulting dysregulated immune response can cause multi-level impairment in the maternofetal and brain barriers and the developing brain itself leading to dysfunction or even loss of several cell populations. Thus, maternal viral infections can disturb brain development and even predispose to neurodevelopmental disorders. In this review, we discuss the potential contribution of maternal viral infections of three relevant relative recent players in the field: Zika, Chikungunya, and Severe Acute Respiratory Syndrome Coronavirus-2, to the impairment of brain development throughout the entire route.